2019
DOI: 10.1002/chem.201900312
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Dependent Nanostructures Based on Active π‐Aggregation Induced Emission Enhancement of New Carbazole Derivatives of Triphenylacrylonitrile

Abstract: In the present study, the carbazole and 2,3,3‐triphenylacrylonitrile (TPAN) nanostructures (2‐CTPAN and 2,2′‐CTPAN) have been designed and synthesized by Pd‐catalyzed Sonogashira cross‐coupling reaction. CTPAN exhibit aggregation‐induced emission enhancement (AIEE) behavior in water with high fluorescence quantum yield. Both the compounds show tunable self‐assembly in water as well as in N,N‐dimethylformamide (DMF) by extended π–π stacking interactions. CTPAN can be self‐assembled into spherical particles in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…As a chromophore with rigid π‐conjugated planes, carbazole and its derivatives have potential applications as good PIs with excellent photoelectric properties and electron delocalization . Xu et al designed and synthesized a series of carbazole‐based oxime ester (OXE) PIs that exhibit excellent photoinitiating properties with a maximum absorption of 330 nm.…”
Section: Introductionmentioning
confidence: 99%
“…As a chromophore with rigid π‐conjugated planes, carbazole and its derivatives have potential applications as good PIs with excellent photoelectric properties and electron delocalization . Xu et al designed and synthesized a series of carbazole‐based oxime ester (OXE) PIs that exhibit excellent photoinitiating properties with a maximum absorption of 330 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds based on carbazole [17][18][19] or triphenylamine [20,21] moieties substituted by tetraphenylethene and/or triphenylethene units were previously reported to show AIE or AIEE effects. Due to the specific linkage topology, some of them displayed blue/sky-blue fluorescence [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…13 Carbazole derivatives are usually employed as an electronic-donor group and they exhibit good absorption and fluorescence. 14,15 Until now, research on carbazole derivatives focuses on π−π orbital interaction, and so far, only one study on carbazolyl−arysilane connected by the N−Si bond has been reported for OLEDs and its structure/ property relationships have not been fully explored. 16,17 Moreover, no conjugated molecules containing a carbazolyl group and Si bridged by the C−Si bond have ever been reported before.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Carbazole-based compounds have attracted considerable attention as hole-transporting and light-emitting materials in scientific and industrial fields . Carbazole derivatives are usually employed as an electronic-donor group and they exhibit good absorption and fluorescence. , Until now, research on carbazole derivatives focuses on π–π orbital interaction, and so far, only one study on carbazolyl–arysilane connected by the N–Si bond has been reported for OLEDs and its structure/property relationships have not been fully explored. , Moreover, no conjugated molecules containing a carbazolyl group and Si bridged by the C–Si bond have ever been reported before. Understanding the effect of the smallest electronic building blocks represents a crucial step toward the development of new functionalized materials.…”
Section: Introductionmentioning
confidence: 99%